Reassessment of Immune Correlates in Human Visceral Leishmaniasis as Defined by Cytokine Release in Whole Blood - Singh, Om Prakash (American Society for Microbiology, 2012)
Depressed cell-mediated immunity in human visceral leishmaniasis (VL) (also known as kala-azar), revealed as the inability of peripheral blood mononuclear cells (PBMCs) to respond to Leishmania antigen, remains a hallmark of and is thought to underlie the progressive nature of this disease. We recently reported the ability of a whole-blood, gamma interferon (IFN-γ) release assay to detect subclinical infections among healthy individuals living in an area where kala-azar is endemic (Bihar, India) and the surprising result that patients with active VL also secreted significant levels of antigen-specific IFN-γ in this assay. We were interested in ascertaining whether these findings would be true for a larger cohort of subjects and in employing the whole-blood assay to detect additional cytokines that might better correlate with the disease status of infected individuals. We evaluated IFN-γ, tumor necrosis factor alpha (TNF-α), and interleukin-10 (IL-10) release in 35 patients with active VL, 54 patients with VL who were cured, 27 patients with other diseases, 52 healthy controls who lived in regions where VL or kala-azar is not endemic (NEHCs [for nonendemic healthy controls]), and 147 healthy controls who lived in regions where kala-azar is endemic (EHCs [for endemic healthy controls]). The cellular responses of the EHCs were correlated with their serological antibody titers against Leishmania donovani and Phlebotomus argentipes saliva. The whole-blood cells from the majority of both active (80%) and cured (85%) VL patients, as well as 24% of EHCs with presumed subclinical infections, produced significantly elevated levels of IFN-γ. The findings do not support a severe Th1 response defect in kala-azar. Importantly, only the patients with active VL also produced IL-10, which in conjunction with IFN-γ better reflects the immune responses that distinguish individuals with active disease from cured or subclinically infected, immune individuals.